Anti-pancreatic Cancer potential of Secalonic acid derivatives from Endophytic Fungi isolated from Ocimum basilicum - Shoeb, M; Hoque, ME; Thoo-Lin, PK; Nahar, N (Dhaka University Journal of Pharmaceutical Sciences, 2014)
The word endophyte means in the plant and refers to all microorganisms that live in the intercellular spaces of stems, petioles, roots and leaves of plants causing no apparent symptoms of disease. Seven endophytic fungi were isolated from the medicinal plant of Ocimum basilicum L. The fungal strain, labeled as 2L, was cultivated at large scale on the potato dextrose agar semi solid medium and was extracted with ethyl acetate. Normal phase silica gel column chromatography of the ethyl acetate extract afforded ergosterol (1), secalonic acid A (2) and secalonic acid D (3). The structures of these compounds (1-3) were elucidated unequivocally by UV, IR, MS, a series of 1D & 2D NMR analyses. The cytotoxicity of these compounds was evaluated by the MTT assay against human pancreatic cancer cell line. Secalonic acid A and secalonic acid D exhibited significant anti-pancreatic cancer activity with IC50 values of 7.3 and 1.6 ?M, respectively. Dhaka Univ. J. Pharm. Sci. 12(2): 91-95, 2013 (December) DOI: http://dx.doi.org/10.3329/dujps.v12i2.17624